IMPROVING STUDENTS ACHIEVEMENT IN READING COMPREHENSION BY APPLYING THE TABA MODEL - Iis Aprianti (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2014)
The objective of this study was to investigate whether the application of Taba model improve the students’ achievement in Reading Comprehension. This study was an classroom action research. The subject of this study was class VIII SMP Negeri 1 Bandar which consisted of 32 students. The study was conducted in two cycles, cycle I consisted of three meetings and cycle II consisted of three meetings. The instruments for collecting data were quantitative data (reading comprehension test) and qualitative data (observation sheert, and questionnaire sheet). Based on reading comprehension scores, students’ score kept improving in every evaluation and based on the observation sheet, and questionnaire sheet it was found that teaching and learning process ran well. Students could enlarge their thinking process. The result of this study showed that the Taba Model improved the students’ achievement in reading comprehension.   Keyword: reading comprehension, taba model, classroom action research.